Personality Change from Life Experiences: Moderation Effect of Attachment Security1. (5th February 2016) - Kawamoto, Tetsuya
Abstract: This study focused on effects of life experiences on change in personality and moderation effects of attachment security on the life experience influences. With a sample of Japanese university students ( N = 1, 000; 679 female; M = 19.72; SD = 1.26; age range, 18–25 years), the Big Five personality traits were assessed twice. The assessment interval was 20 weeks. Hierarchical linear modeling (HLM) analyses revealed that there were large between‐individual differences in change and stability of the Big Five personality traits, which were accounted for by the amount of daily positive and negative life experiences during the interval period. Moreover, multi‐group HLM analyses indicated that the life experience effects were moderated by participants' attachment security at Time 1. These findings suggest that the accumulation of small daily experiences may work for the personality development of university students and that environmental influences may vary by individual susceptibility to experiences, like attachment security.